LEARNING IN VIRTUAL ENVIRONMENTS, EXPRESSION OF EDUCATIONAL EFFICIENCY AND QUALITY - Emil LAZĂR (Universitaria Publishing House, Craiova, 2020)
The arising question, within the context of this debate, is related to the concordance between school learning and students real life (utility and concordance with the individuality/ the dimensions of students personality. The issue includes multiple topics of discussion. Virtual learning environments is a set of teaching-learning and evaluation tools designed to expand learning experiences through the use of ICT tools. We understand an integrated construction of the different elements that constitute the virtual learning environment.